Neglected exposure route: cobalt on skin and its associations with urinary cobalt levels - Kettelarij, Jolinde; Midander, Klara; Lidén, Carola; Bottai, Matteo; Julander, Anneli (Occupational and environmental medicine (London, England), 2018)
ObjectivesCobalt (Co) exposure is associated with adverse health effects including skin sensitisation, asthma and interstitial lung fibrosis. Exposure to Co in industrial settings is often assessed using air samples or biomonitoring in urine. Skin exposure is rarely measured. Aim of this study was to quantify and compare the importance of Co skin exposure and respiratory exposure in determining urinary Co concentrations.MethodsCo skin exposure was measured in 76 hard metal workers by acid wipe sampling before and at the end of work shifts. Spot urine was collected during a 24-hour period from the start of a shift. Respiratory exposure was measured by personal inhalable dust sampling during a shift in 30 workers. Co was analysed by inductively coupled plasma mass spectrometry.ResultsQuantile regression modelling showed that a doubling of Co on skin before or at the end of shift increased the median urinary concentration of Co by 70% (p<0.001) or 32% (p<0.001), respectively. A doubling of Co in air increased median urinary Co by 38% (p<0.001). Co skin exposures were still significantly associated with urinary Co after excluding a group of workers with high respiratory exposure (33%, p=0.021 and 17%, p=0.002).ConclusionsThe results indicate an association between Co skin exposure and urinary Co concentrations. This should be considered when using urinary Co as a biomarker of exposure.